RANCANG BANGUN SISTEM PENGENDALI TEMPERATUR DENGAN PROPORSIONAL, INTEGRAL DAN DIFERENSIAL (PID) BERBASIS MIKROKONTROLER ARDUINO UNO - Noviyani, Siti; Sumariyah, Sumariyah (BERKALA FISIKA, 2019)
The aim of this research was to realize a design of a temperature control system with the proportional-integral-differential (PID) based on the Arduino Uno microcontroller, and toanalyz e the PID to the system. The PID control method was designed by identifying plants using the Ziegler-Nichols method to determine PID parameters consisting of proportional constant (Kp), integral constant (Ti), and differential determination constant (Td). Hardware design consisted of the Arduino Uno microcontroller which is open source with PID and pulse width modulation (PWM), and it can be control with feedback in the form of temperature sensors, AC lamp generators, and AC dimmer lamps. The system was implemented using C language with Arduino IDE software. The system can be done at the best stability point with a value of Kp = 0.015, Ti = 101.52, Td = 25.38. The three parameters have their respective functions, i.e. Kp is used to small error detector, Ti is to back-up system in order to work around the set-point, and Td is to speed up the system rate.Keywords: PID, temperature, Ziegler-Nichols method, Arduino Uno